Separatyzm językowy w Hiszpanii - Skobrtal, Marcin (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
Language is one of the most important features distinguishing a nation. Its role and position in the public sphere determines the level of autonomy of every stateless nation. After the death of Francisco Franco in 1975, Spain experience a revival of such nations as Catalans, Basques and Galicians. This revival has resulted in the natives’ demands for their languages to be recognized as official ones and be granted this particular status. This article describes the latest efforts and problems in this domain, the linguistic situation of the particular regions, as well as the legal status of each. The main aim of this article is to characterize these phenomena and to reveal in what way these demands have affected the structure of the Spanish state.